Cardiorespiratory fitness and walking endurance improvements after 12 months of an individualised home and community-based exercise programme for people after stroke. (15th October 2017) - Dunn, Ashlee; Marsden, Dianne L; Barker, Daniel; Van Vliet, Paulette; Spratt, Neil J; Callister, Robin
ABSTRACT: Objective : To evaluate the immediate and longer-term effects of an individually tailored, home- and community-based exercise programme with ongoing remote support in people with stroke on cardiorespiratory fitness (CRF), ambulation and health-related quality of life (HRQoL). Methods : Twenty people 5.3 ± 3.5 months post stroke completed the 12-week HowFITSS? exercise programme aimed at increasing CRF and daily physical activity. Support was provided by phone and email, which decreased in frequency over time. Participants were assessed at baseline, then at 3, 6 and 12 months after initiation of the intervention. CRF (VO2peak ) was evaluated using a portable metabolic system during the 6-minute walk test (6MWT), the Shuttle Walk Test (SWT) and the cycle graded exercise test (cGXT). Walking speed, balance, body composition, fatigue, depression and HRQoL were also measured. Results : CRF improved significantly from pre-intervention to 12-month follow-up on the 6MWT (Effect Size, ES = 0.87; p = 0.002) and cGXT (ES = 0.60; p < 0.001), with more modest improvements on the SWT (ES = 0.52; p = 0.251). From baseline to 12 months, significant within-participant improvements were found for self-selected walking speed, balance and HRQoL. Performances on the remaining tests were maintained over the post-intervention period. Conclusion : There may be health benefits of providing people with stroke an exercise intervention with long-term support that encourages increased regular physical activity.